An Analysis of SAFER - Murphy, Sean (Journal of cryptology, 1998)
We investigate some of the algebraic properties of the SAFER block cipher when the message space is considered as a Z -module. In particular, we consider the invariant Z -submodules of the PHT layer and show how these invariant Z -submodules give potential cryptographic weaknesses.